2010
DOI: 10.1007/s00264-010-1115-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in the femoral neck increases after hip resurfacing: a cohort with five-year follow-up

Abstract: Hip resurfacing is an effective treatment modality for arthritis of the hip in carefully selected patients; however, its use remains controversial due to its higher revision rates compared with conventional total hip replacement surgery. The most frequent reason for revision is femoral neck fracture, and preoperative bone mineral density is an important factor when considering the option of hip resurfacing. Whilst reduction in bone mineral density following total hip replacement is well documented, little is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…However, the increment in BMD in the continuing years, as reported in other studies, [ 29 , 30 , 31 ] was in contrast to this study. A minimal reduction was expected in the following years, similar to that projected in the hip OA and THA femurs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the increment in BMD in the continuing years, as reported in other studies, [ 29 , 30 , 31 ] was in contrast to this study. A minimal reduction was expected in the following years, similar to that projected in the hip OA and THA femurs.…”
Section: Discussioncontrasting
confidence: 99%
“…As the resurfacing techniques involved the modification of the femoral head and neck, the proximal region of the femur was expected to experience more changes. Willis-Owen et al [ 29 ] reported that the BMD of the femoral neck only decreased in the first three months, and then kept increasing for at least five years. A comparison study between THA and RHA by Kishida et al [ 30 ] also found an increase in BMD in Gruen 1 and 7 following hip arthroplasty, while there was a BMD reduction following total replacement for two years.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of HR advocate several advantages over standard total hip replacement (THR) which include: preservation of femoral bone stock which makes revision of the femoral side easier at a later date [2]; better stability because of the large head diameter [3]; less abnormal loading of the upper femur and femoral stress shielding [4]; superior functional outcome which allows high impact sport resumption; and higher survival in selected patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…We admired the work of Willis-Owen and his colleagues on bone remodelling after hip resurfacing presented in their article "Bone mineral density in the femoral neck increases after hip resurfacing: a cohort with five-year follow-up" [1]. Hip resurfacing has evolved as an alternative to total hip arthroplasty in young adults and has shown promising short-and mid-term results when prudent selection criteria were adopted.…”
mentioning
confidence: 99%